Preparing and Analyzing Solitons in the Sine-Gordon Model with Quantum Gas Microscopes - Elisabeth Wybo; Alvise Bastianello; Monika Aidelsburger; Immanuel Bloch; Michael Knap (PRX Quantum, 2023)
The sine-Gordon model emerges as a low-energy theory in a plethora of quantum many-body systems. Here, we theoretically investigate tunnel-coupled Bose-Hubbard chains with strong repulsive interactions as a realization of the sine-Gordon model deep in the quantum regime. We propose protocols for quantum gas microscopes of ultracold atoms to prepare and analyze solitons, which are the fundamental topological excitations of the emergent sine-Gordon theory. With numerical simulations based on matrix product states, we characterize the preparation and detection protocols and discuss the experimental requirements.